Cross-border bank M&As and risk: evidence from the bond market - Sungho Choi; Bill B. Francis; Iftekhar Hasan (Bank of Finland, 2010)
The impact of cross-border bank M&As on bank risk remains an open question. Though geographically diversifying bank M&As have the potential to reduce the risk of bank insolvency, they also have the potential to increase that risk due to the increase in risk-taking incentives for bank managers and stockholders following these transactions. This paper empirically investigates whether cross-border bank M&As increase or decrease the risk of acquiring banks as captured by changes in acquirers yield spreads. The paper also investigates how differences in the institutional environments between bidder and target countries affect changes in yield spreads following M&A announcements. The study finds that bondholders, in general, perceive cross-border bank M&As as risk-increasing activities, unlike domestic bank mergers. Specifically, on average, yield spreads increase by 4.13 basis points following the announcement of cross-border M&As. This study also finds that these yield spreads are significantly affected by the differences in investor-protection and deposit-insurance environments between the transacting countries. However, the study does not find that the regulatory and supervisory environment in the home countries of the transacting parties significantly affects the changes in yield spreads. The overall evidence suggests that regulators should judge the relative environment in both the home and the host countries in evaluating the associated risks of an active multinational financial institution and in setting the sufficiency of the banks reserve positions.
URN:NBN:fi:bof-20140807205
Keywords: 330